Low Power Networks-on-Chip - Silvano, Cristina; Lajolo, Marcello; Palermo, Gianluca; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2011)
Low Power Networks-on-Chip Edited by: (editors) Cristina Silvano Marcello Lajolo Gianluca Palermo In recent years, both Networks-on-Chip, as an architectural solution for high-speed interconnect, and power consumption, as a key design constraint, have continued to gain interest in the design and research communities, since power and energy issues still represent one of the limiting factors in integrating multi- and many-cores on a single chip. This book covers power and energy aware design techniques from several perspectives and abstraction levels and offers a single-source reference to some of the most important design techniques proposed in the context of low-power design for networks-on-chip architectures. •Describes the most important design techniques that were invented, proposed, and applied to reduce both dynamic power and static power dissipation in networks-on-chip based architectures; •Applies state-of-the-art, low-power design techniques to the design of Networks-on-Chip, to demonstrate methodology for design of high-speed, low-power interconnect; •Offers a single source reference to the latest research, otherwise available only in disparate journals and conference proceedings.
Network-on-Chip Power Estimation -- Timing -- synchronous/asynchronous communication -- Network-on-Chip link design -- Topology exploration -- Network-on-Chip support for CMP/MPSoCs -- Network design for 3D stacked logic and memory -- Beyond the wired Network-on-Chip.
Keywords: Electronic circuits; Computer-aided engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design